Increased Sensitivity to Alcohol Induced Changes in ERK Map Kinase Phosphorylation and Memory Disruption in Adolescent as Compared to Adult C57BL/6J Mice - Spanos, Marina (2012)
Adolescence is a critical period of brain development that is accompanied by increased probability of risky behavior, such as alcohol use. Emerging research indicates that adolescents are differentially sensitive to the behavioral effects of acute ethanol as compared to adults but the neurobiological mechanisms of this effect remain to be fully elucidated. This study was designed to evaluate effects of acute ethanol on extracellular signal-regulated kinase phosphorylation (p-ERK1/2) in mesocorticolimbic brain regions. We also sought to determine if age-specific effects of ethanol on p-ERK1/2 are associated with ethanol-induced behavioral deficits on acquisition of the hippocampal-dependent novel object recognition (NOR) test. Adolescent and adult C57BL/6J mice were administered acute ethanol (0 0.5, 1, or 3 g/kg, i.p.). Brains were removed 30-min post injection and processed for analysis of p-ERK1/2 immunoreactivity (IR). Additional groups of mice were administered ethanol (0 or 1 g/kg) prior to the NOR test. Analysis of p-ERK1/2 IR showed that untreated adolescent mice had significantly higher levels of p-ERK1/2 IR in the nucleus accumbens shell, basolateral amygdala (BLA), central amygdala (CeA), and medial prefrontal cortex (mPFC) as compared to adults. Ethanol (1 g/kg) selectively reduced p-ERK1/2 IR in the dentate gyrus and increased p-ERK1/2 IR in the BLA only in adolescent mice. Ethanol (3 g/kg) produced the same effects on p-ERK1/2 IR in both age groups with increases in CeA and mPFC, but a decrease in the dentate gyrus, as compared to age-matched saline controls. Pretreatment with ethanol (1 g/kg) disrupted performance on the NOR test specifically in adolescents, which corresponds with the ethanol-induced inhibition of p-ERK1/2 IR in the hippocampus. These data show that adolescent mice have differential expression of basal p-ERK1/2 IR in mesocorticolimbic brain regions. Acute ethanol produces a unique set of changes in ERK1/2 phosphorylation in the adolescent brain that are associated with disruption of hippocampal-dependent memory acquisition.